Pencegahan Perundungan di Sekolah melalui Character Building dalam Pendekatan Al-Qur’an - Ibnu Awwaliansyah; Akhmad Shunhaji (Dakwah Institut PTIQ Jakarta, 2022)
The problem of bullying as communication behavior in Indonesia for students is increasing at school. Based on many studies that have been carried out, the cause is the absence of character building which is internalized in students, so the need for comprehensive, effective and appropriate prevention. Because, there have been many strategies, methods, models, and techniques that have been carried out by various experts, it seems that they have not been very effective in solving bullying behavior in schools that are already very critical. The Al-Qur'an approach is the right and accurate choice in providing solutions for preventing bullying in schools without negating the theories, models and concepts of bullying and character education that have been initiated and carried out by experts. The purpose of this study is to analyze the prevention of bullying in schools through Al-Qur'an-based character education. The theoretical framework used is humiliation theory in bullying and humanistic theory in character education. Meanwhile, the methodology used is a qualitative approach with a literature study method. The analytical technique is thematic analysis. The results show that the prevention of character education in bullying has been explained in depth and comprehensively, both in His verses, commentators and hadiths. Bullying is an inhuman act and is a major sin as contained in the surah and al hamz and al lamz means to reproach (Al Humazah/104:1), as sukhriyah means to humiliate (Al Hujurat/49:11), yadhhakûn from adh dhahak means laughing (Al Mutaffifin/83:29), al-ghamz means gesturing with his eyes aimed at condescending (Al Mutaffifin/83:30), and others.